Growth Performance of Tilapia Oreochromis niloticus with the Provision of GDM Probiotics maintained with the Biofloc System - Hadijah, Hadijah; Gatta, Ratnawati; ., Rusmin (Hasanuddin University, 2022)
Tilapia is one type of freshwater fish that has economic value. This type of fish has good adaptability and fast growth. One of the problems in tilapia cultivation is that probiotics have not been utilized in the maintenance media with a biofloc system. This study aimed to determine the dose of probiotic supplementation in the formation of bioflocs on the growth and survival of tilapia. The research was conducted at the Educational Pond, Bosowa University, Maros Regency. The test animals used were tilapia seeds measuring 2-3 cm long. The stocking density of 3 seeds/L were kept in a basin with a capacity of 80 L filled with 60 L of water. The treatment tested was GDM probiotic supplementation in media with doses of A 5%, B 6%, C 7%, and D 0 %. The study used a completely randomized design with 4 treatments and 3 replications so that there were 12 experimental units. Seeds were reared for 60 days by feeding Hi-Pro-Vite FF-99 as much as 3% of body weight biomass per day. The results showed that GDM probiotic supplementation with different doses significantly affected the growth and survival of tilapia. Supplementation of GDM probiotics 5%, 6% and 7% in the media gave the same effect on the growth and survival of tilapia but significantly different from the treatment without probiotics. The highest growth and survival rate of tilapia was obtained at a dose of 5%, 4.27g and 65%, respectively, while the lowest was in the treatment without probiotics, namely 3.27g and 48.33%. Based on the results of the study, it is recommended that 5% GDM probiotic supplementation in tilapia rearing containers is recommended.